Precedentes judiciais e segurança jurídica: caminhos para uma justiça eficiente - Silva, Marcelo Fernandes e (2020)
In the last decades, the Brazilian Judiciary Power has acquired an important role in the social and political scene, insofar as it has solved relevant issues that were not the object of appreciation by the Legislative Power. This role has its origin in the guarantee of access to justice provided by the Constitution and also in the inertia of the other Powers. However, this role played by the Judiciary, primarily by the Federal Supreme Court, has a harmful aspect that can be noticed in the lack of reasoning of some decisions and the large number of divergent decisions in similar cases, thus generating legal uncertainty. An alternative to improve this situation would be the implementation of the Precedent System in the Brazilian Legal System. Due to this, it is necessary to analyze how to apply it in a system that has the law as the main source, in view of the origin of the precedents being in the Common Law system, in order to seek greater effectiveness to the jurisdiction. Thus, in view of the changes adopted by the Civil Procedure Code, the means must be applied so that there is a conciliation between access to justice for all those subject to jurisdiction and the guarantee that the process will safeguard legal security, equality and speed, developing an effective judiciary, given the needs of society.